Evaluasi Kebijakan Pengendalian Deforestasi dalam Mencapai Target Pembangunan Berkelanjutan (SDGs) - Mawaddah Mawaddah; Zulkarnaini Zulkarnaini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Deforestation remains a critical challenge for sustainable development in Indonesia. This study evaluates the effectiveness of deforestation control policies in supporting the achievement of SDG Target 15.2 on sustainable forest management. Using a qualitative approach with the DPSIR (Drivers-Pressures-State-Impacts-Responses) analytical framework, the research examines policy documents, government reports, and deforestation datasets from Global Forest Watch. The results indicate that while policies such as the forest moratorium and the FOLU Net Sink 2030 commitment have successfully reduced deforestation in priority areas, their implementation continues to face complex challenges. Key findings reveal: (1) Economic incentive disparities between central and local governments drive forest exploitation for local revenue; (2) Weak multi-sectoral coordination between forestry policies and infrastructure development; (3) Limited community participation in decision-making processes; and (4) Real-time monitoring systems that are not yet integrated with rapid response mechanisms. The study recommends strengthening green incentives, enhancing collaborative governance, recognizing indigenous community rights, and optimizing monitoring technologies as strategies to accelerate SDG achievement. These findings make significant contributions to environmental policy literature by offering a holistic perspective on deforestation control challenges in developing countries.